The Effect of Capital, Accounting Knowledge and Accounting Training on MSMEs in Using Accounting Information Systems Palembang City - Resky Ramadhani; Harsi Romli; RM. Rum Hendarmin (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to examine the effect of capital, accounting knowledge, and accounting training on the use of accounting information systems in MSME Palembang. The sample utilized the Simple Random Sampling technique. The data in the study amounted to 100 respondents. Data collection techniques utilized a questionnaire. Data analysis utilized multiple linear regression. The results of the study prove that capital, accounting knowledge, accounting training have an effect on the variables of using accounting information in MSME Palembang. This research is expected to provide benefits for MSME owners to pay attention to capital, accounting knowledge and accounting training to increase the use of accounting information systems for MSME in Palembang.